DENGUE OUTBREAK IN MATO GROSSO STATE, MIDWESTERN BRAZIL - HEINEN, Letícia Borges da Silva; ZUCHI, Nayara; CARDOSO, Belgath Fernandes; SANTOS, Marcelo Adriano Mendes dos; NOGUEIRA, Mauricio Lacerda; DEZENGRINI-SLHESSARENKO, Renata (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Dengue virus (DENV) is the most frequent arbovirus worldwide. In this study, we report a large outbreak in Mato Grosso State (MT). Serum samples from 604 patients with acute febrile illness for less than five days were inoculated in C6/36 cells, then infected cells were subjected to an indirect immunofluorescence test for DENV serotypes and yellow fever virus. Serum samples were submitted to a multiplex-semi-nested-RT-PCR for 11 flaviviruses. DENV-4 was isolated in 150/604 (24.8%) and DENV-1 in 19/604 (3.1%) specimens. By RT-PCR, 331 (54.8%) samples tested positive for DENV; 321 had single infections (DENV-4 n = 305; DENV-1 n = 15; DENV-3 n = 1), nine had co-infections of DENV-1/DENV-4, and one of DENV-2/DENV-4. DENV-4 was detected in 315/331 (95.2%) positive patients from 17 municipalities, and DENV-1 in 24/331 (7.2%) patients from five cities in north-central MT and the city of Cuiaba. The incidence of infection was higher in patients aged 20-39 (142/331; 42.9%). The NS5 partial nucleotide sequence of DENV-1 was most similar to that of genotype V, DENV-2 to Southeast Asian/American, DENV-3 to genotype III, and DENV-4 to genotype II strains, considered the most frequent strains in Brazil. This outbreak coincided with the introduction of DENV-4 in the state. Cuiaba was hyperendemic for the four DENV serotypes, highlighting the necessity for arbovirus surveillance in MT.